2012
DOI: 10.1088/0741-3335/54/8/085012
|View full text |Cite
|
Sign up to set email alerts
|

Global gyrokinetic turbulence simulations of MAST plasmas

Abstract: Abstract. Local and global electrostatic gyrokinetic simulations of MAST spherical tokamak for ITG modes with adiabatic electron response find good agreement in linear stability with growth rates below the experimental E × B shearing rate. The kinetic treatment of electrons is shown to increase the growth rates above the shearing rate. The collisionless simulations with kinetic electrons and experimental flow shear find unstable modes in the outer part of the plasma. In global simulations the flow shear stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 25 publications
(44 reference statements)
2
34
0
Order By: Relevance
“…The fluctuation level δn e /n e exhibits similar behaviour. The underprediction in the core is consistent with the previous linear studies [21], which showed the region whereŝ ≤ 0 to be linearly stable. The effect of including equilibrium flow shear (III) in the simulations with kinetic electrons is not dramatic, with a slight decrease in Q sim i compared to case II in the core where the flow shear is strongest, but an increase in the peripheral region, where Q sim i approaches the experimental level -the corresponding changes in δn e /n e are rather slight.…”
Section: Turbulence Amplitudes and Ion Heat Fluxessupporting
confidence: 91%
See 3 more Smart Citations
“…The fluctuation level δn e /n e exhibits similar behaviour. The underprediction in the core is consistent with the previous linear studies [21], which showed the region whereŝ ≤ 0 to be linearly stable. The effect of including equilibrium flow shear (III) in the simulations with kinetic electrons is not dramatic, with a slight decrease in Q sim i compared to case II in the core where the flow shear is strongest, but an increase in the peripheral region, where Q sim i approaches the experimental level -the corresponding changes in δn e /n e are rather slight.…”
Section: Turbulence Amplitudes and Ion Heat Fluxessupporting
confidence: 91%
“…Results of runs incorporating electron collisions, which had been shown to reduce the linear drive due to trapped electrons [34], were not reported in Ref. [21] (simulations with collisions have however been peformed for the more recent equilibrium discussed in §2.2.2).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…The turbulence predicted by our simulations is, therefore, only representative of the turbulence at a single flux surface, even though our box sizes can be the size of MAST (several such formally overlapping simulations can be then used to model transport across the entire radial extent of the machine). For the MAST discharge and radial location studied in this work, one finds ρ i /a ∼ 1/100, where ρ i ≈ 6×10 −3 m and a ≈ 0.6 m. While this is a reasonably small number, previous studies of simpler geometries have suggested that non-local effects can reduce the level of turbulent transport by 50% at values similar to 1/100 [63,64]. A scan of different values of ρ * using a global gyrokinetic code would be required to test whether non-local effects change the level of turbulence for the MAST turbulence studied in this paper.…”
Section: Local Gyrokinetic Descriptionmentioning
confidence: 48%